Association Between Night-Shift Work and Cancer Risk: Updated Systematic Review and Meta-Analysis - Dun, Aishe (Front Oncol, 2020)
Background: Nightshift work introduces light at night and causes circadian rhythm among night workers, who are considered to be at increased risk of cancer. However, in the last 2 years, nine population-based studies reported insignificant associations between night-shift work and cancer risks. We aimed to conduct an updated systematic review and meta-analysis to ascertain the effect of night-shift work on the incidence of cancers. Methods: Our protocol was registered in PROSPERO and complied with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Embase, PubMed, and Web of Science databases were used to comprehensively search studies published up to May 31, 2019. The random-effect model (Der Simonian-Laird method) was carried out to combine the risk estimates of night-shift work for cancers. The dose-response meta-analysis was performed to verify whether the association was in a dose-dependent manner. Results: Our literature searching retrieved 1,660 publications. Included in the meta-analyses were 57 eligible studies with 8,477,849 participants (mean age 55 years; 2,560,886 men, 4,220,154 women, and 1,696,809 not mentioned). The pooled results showed that night-shift work was not associated with the risk of breast cancer (OR = 1.009, 95% CI = 0.984–1.033), prostate cancer (OR = 1.027, 95% CI = 0.982–1.071), ovarian cancer (OR = 1.027, 95% CI = 0.942–1.113), pancreatic cancer (OR = 1.007, 95% CI = 0.910–1.104), colorectal cancer (OR = 1.016, 95% CI = 0.964–1.068), non-Hodgkin's lymph (OR = 1.046, 95% CI = 0.994–1.098), and stomach cancer (OR = 1.064, 95% CI = 0.971–1.157), while night-shift work was associated with a reduction of lung cancer (OR = 0.949, 95% CI = 0.903–0.996), and skin cancer (OR = 0.916, 95% CI = 0.879–0.953). The dose-response meta-analysis found that cancer risk was not significantly elevated with the increased light exposure of night- shift work. Conclusion: This systematic review of 57 observational studies did not find an overall association between ever-exposure to night-shift work and the risk of breast, prostate ovarian, pancreatic, colorectal, non-Hodgkin's lymph, and stomach cancers.